SPICE Modeling and Simulation of a MPPT Algorithm - Miona Andrejević Stošović (Electronics, 2014)
One among several equally important subsystems of a standalone photovoltaic (PV) system is the circuit for maximum power point tracking (MPPT). There are several algorithms that may be used for it. In this paper we choose such an algorithm based on the maximum simplicity criteria. Then we make some small modifications to it in order to make it more robust. We synthesize a circuit built out of elements from the list of elements recognized by SPICE. The inputs are the voltage and the current at the PV panel to DC-DC converter interface. Its task is to generate a pulse width modulated pulse train whose duty ratio is defined to keep the input impedance of the DC-DC converter at the optimal value.